ASSERTIVE TRAINING THERAPY FOR SCHIZOPHRENIC PATIENT WITH RISK OF VIOLENT BEHAVIOR: Doi: https://doi.org/10.35654/ijnhs.v2i2.85 - Safra Ria Kurniati; Novy Helena Catharina Daulima (International Journal of Nursing and Health Services (IJNHS), 2019)
Violent behavior is one of the symptom of severe mental disorders such as schizophrenia. Violent behavior has a very significant impact not only for patients, but also health care professionals, families and the development of stigma in society. Assertive training therapy is one therapy that is still not largely used for patients with violent behavior in Indonesia, although it is not an uncommon situation. This case is quite challenging considering the patient has a lack of insight of the disease. After completing 5 sessions of therapy, the patient showed improvement in signs and symptoms, a stable condition, and the absence of symptoms of violent behavior during treatment. For this reason, the use of therapy is highly recommended to help patients to express themselves in a more adaptive way.